Perubahan Ukuran Linear Tubuh Kambing Kacang Jantan yang diberikan Silase Komplit Berbahan Dasar Hijauan Sorgum, Rumput Raja dan Rumput Alam - Stefanus Naitili; Paulus K. Tahuk; Gerson F. Bira (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
The purpose of this study was to determine changes in the linear body size of male goats which were given complete silage based on Sorghum bicolor, Pennisetum purpuphoides and natural grass. The variables studied were body length, chest circumference, and shoulder height. The research method used was a Completely Randomized Design with the treatment given was TI: Sorghum bicolor 45% + Leucaena leococephala 20% + Corn 25% + pollard 10%, T2: Natural Grass 45% + Leucaena leococephala 20% + Corn 25% + Pollard 10%, Q3: Pennisetum purpuphoides 45% + Leucaena leococephala 20% + Corn 25% + pollard 10%. The results showed that shoulder height, body length and chest circumference in male goat goats for the three treatments using natural grass-based (T1), Pennisetum purpuphoides (T3) and Sorghum bicolor (T2) silage feed showed relatively similar results and had no effect. real. It was concluded that the use of different forages (natural grass, Sorghum bicolor, and Pennisetum purpuphoides) as the basis for making complete silage can increase the linear growth of a relatively similar body of goat nuts. The use of Sorghum bicolor (T2) in the manufacture of complete silage showed a higher body length, chest circumference, and shoulder height between treatments (T1 and T3).